Initial and Continued Airworthiness: Commonalities and Differences Between Civil and Military Aviation - Rafael Luterbacher Mus; Rebecca Rodeck; Gerko Wende (Aerospace)
Besides the fact that civil and military aerospace are governed by the same physics and design fundamentals, differences exist between the initial and continued airworthiness criteria for these two aviation fields. Whereas civil aerospace is highly regulated by national and international organizations, the military is mainly governed by national regulations or, in multinational projects, by agreed-upon regulations. A trend exists towards the homogenization of rules in both fields; however, due to national security interests, these are generally agreed upon on a case-by-case basis. This review aims to provide an overview of the processes employed for initial and continued airworthiness of civil and military aviation, focusing on the similitudes and differences.